2009
DOI: 10.1021/jf901052e
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationship in the Interaction of Substituted Perinaphthenones with Mycosphaerella fijiensis

Abstract: The levels of native fungitoxic perinaphthenone phytoalexins in susceptible Musa varieties (banana), which are commercially grown in large plantations, are too low to provide plants with long-lasting protection against highly pathogenic fungi. Novel strategies for plant protection are necessary to reduce crop losses and to prevent the development of resistant fungal strains. The synthesis of novel fungicides based on the structures of perinaphthenone natural products is considered to be a promising strategy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…It is possible that some product of the secondary metabolism with direct activity against M. fijiensis is produced by this increased PAL activity. Several studies have shown that some banana cultivars contain secondary metabolites of the type phenylphenalenones that have in vitro activity against M. fijiensis (Otálvaro et al 2007;Hidalgo et al 2009). More recently, a phytoanticipin with strong in vitro activity against M. fijiensis was isolated from leaves of the banana cultivar Grande Naine.…”
Section: Plant Responses To Mycosphaerella Fijiensismentioning
confidence: 99%
“…It is possible that some product of the secondary metabolism with direct activity against M. fijiensis is produced by this increased PAL activity. Several studies have shown that some banana cultivars contain secondary metabolites of the type phenylphenalenones that have in vitro activity against M. fijiensis (Otálvaro et al 2007;Hidalgo et al 2009). More recently, a phytoanticipin with strong in vitro activity against M. fijiensis was isolated from leaves of the banana cultivar Grande Naine.…”
Section: Plant Responses To Mycosphaerella Fijiensismentioning
confidence: 99%
“…The reactions involved perinaphthenone (Escobar 2002;Quiñones et al 2000;Luis et al 1994b) or 3-(2-hydroxynaphthalen-1-yl) propanenitrile, (Hidalgo et al 2009) coupled with an appropriated Grignard reactive (Fig. 3).…”
Section: Synthesis Of Phenylphenalenonesmentioning
confidence: 99%
“…Mycelial growth and spore germination were analyzed in conidias and ascospores (Escobar 2002;Quiñones et al 2000;Escobar et al 2010;Hidalgo et al 2009). The natural compounds displayed a marginal activity but several synthetic analogues, especially perinaphthenone, were more active than phytoalexins until to the fourteenth day of applications of the compounds.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…They are polycyclic aromatic compounds consisting of a tricyclic phenalene core structure with a keto functional group and a lateral phenyl ring (ring D) (see structure in Table 1). Because of their fungicidal (Otálvaro et al, 2007;Hidalgo et al, 2009) and nematicidal properties (Hölscher et al, 2014) and their inducibility after pathogen/herbivore attack (Luis et al, 1994;Jitsaeng and Schneider, 2010;Otálvaro et al, 2010), phenylphenalenones play an important role as phytoalexins in the chemical defense of Musa plants. The physiological and/or ecological importance of these metabolites in the three other plant families has yet to be explored, although their antioxidant capacity could be one of the reasons they are produced (Blokhina et al, 2003;Duque et al, 2010;Brewer, 2011).…”
Section: Introductionmentioning
confidence: 99%